2023
DOI: 10.3390/plants13010030
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Phytochemical Composition and Biological Potential of Balkan Endemic Species Stachys scardica Griseb

Desislava I. Mantovska,
Miroslava K. Zhiponova,
Detelina Petrova
et al.

Abstract: Stachys scardica Griseb. is a Balkan endemic species listed in The Red Data Book of Bulgaria with the conservation status “endangered”. Successful micropropagation was achieved on MS medium supplemented with 1.5 mg/L benzyladenine (BA), followed by a subsequent ex vitro adaptation in an experimental field resulting in 92% regenerated plants. Using nuclear magnetic resonance (NMR), phenylethanoid glycosides (verbascoside, leucosceptoside A), phenolic acids (chlorogenic acid), iridoids (allobetonicoside and 8-OA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…This research is extremely valuable for utilizing such biomass to obtain active secondary metabolites with valuable medicinal properties. The results of these tests are often compared to plant material harvested from soil, and it is preferable for them to be associated with the mother/parent plants [ 45 , 57 , 58 ]. Jakabfi-Csepreg et al [ 59 ] analyzed the antimicrobial activity of an aqueous extract from the leaves of Lathyrus tuberosus , a species used in European and Asian folk medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research is extremely valuable for utilizing such biomass to obtain active secondary metabolites with valuable medicinal properties. The results of these tests are often compared to plant material harvested from soil, and it is preferable for them to be associated with the mother/parent plants [ 45 , 57 , 58 ]. Jakabfi-Csepreg et al [ 59 ] analyzed the antimicrobial activity of an aqueous extract from the leaves of Lathyrus tuberosus , a species used in European and Asian folk medicine.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that both extracts from microshoot and root cultures had cytotoxic effects on cancer cells, similar to the tests performed under this study of S. henryi microshoot culture extract. Mantovska et al [ 58 ] focused on the endemic species Stachys scardica . In vitro microshoot cultures were established, and S. scardica extracts were examined for phytochemical analysis and biological activities.…”
Section: Discussionmentioning
confidence: 99%